Positive Modulation of Angiotensin II Type 1 Receptor–Mediated Signaling by LVV–Hemorphin-7 - Ali, Amanat; Palakkott, Abdulrasheed; Ashraf, Arshida; Al Zamel, Isra; Baby, Bincy; Vijayan, Ranjit; Ayoub, Mohammed Akli (Frontiers in Pharmacology, 2019)
Hemorphins are hemoglobin β-chain-derived peptides initially known for their analgesic effects via binding to the opioid receptors belonging to the family of G protein-coupled receptor (GPCR) as well as their physiological action on blood pressure. However, their molecular mechanisms in the regulation of blood pressure are not fully understood. Studies have reported an anti-hypertensive action via the inhibition of the angiotensin-converting enzyme (ACE), a key enzyme in the renin-angiotensin system (RAS). In this study, we hypothesized that hemorphins may also target angiotensin II (AngII) type 1 receptor (AT1R) as a key GPCR in RAS. To investigate this, we examined the effects of LVV-hemorphin-7 on AT1R transiently expressed in human embryonic kidney (HEK293) cells using bioluminescence resonance energy transfer (BRET) technology for the assessment of AT1R/Gαq coupling and β-arrestin 2 recruitment. Interestingly, while LVV-hemorphin-7 alone had no significant effect on BRET signals between AT1R and Gαq or β-arrestin 2, it nicely potentiated AngII-induced BRET signals and significantly increased AngII potency. The BRET data were also correlated with AT1R downstream signalling with LVV-hemorphin-7 potentiating the canonical AngII-mediated Gq-dependent inositol phosphate pathway as well as the activation of the extracellular signal-regulated kinases (ERK1/2). Both AngII and LVV-hemorphin-7-mediated responses were fully abolished by AT1R antagonist demonstrating the targeting of the active conformation of AT1R. Our data report for the first time the targeting and the positive modulation of AT1R signalling by hemorphins, which may explain their role in the physiology and pathophysiology of both vascular and renal systems. This finding further consolidates the pharmacological targeting of GPCRs by hemorphins as previously shown for the opioid receptors in analgesia opening a new era for investigating the role of hemorphins in physiology and pathophysiology via the targeting of GPCR pharmacology and signalling.